Deteksi Akuifer Air Tanah Menggunakan Metode Geolistrik (Studi Kasus di Politeknik Negeri Lampung) - Didik Kuswadi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2019)
In fact, the interpretation of groundwater potential is not as easy as it is predicted, even often quite difficult and requires elaborate equipment. This remembers the formation and movement of groundwater in nature, so that measurements cannot be carried out directly. Interpretation of groundwater potential will always include two main objectives, namely: (1) soils or rocks as a medium where groundwater is acquired, and (2) groundwater as a liquid that fills the cavity in the soil or rocks. Some ground level investigation methods that can be done, including: Geological method, Gravity method, Magnetic field method, seismic method, and Geoelectric method. From these methods, the Geoelectric method is a very widely used method and the result is quite good. These geoelectric estimates are intended to obtain an overview of the subsurface of the soil and the possibility of groundwater and minerals at a certain depth. These geoelectric estimates are based on the fact that different materials will have different types of prisoners when they are electrically flowing. Groundwater has a lower type of prisoner than mineral rocks. The objectives of the study are: (1) Identifying soil layer formations and precise drilling depth at points of observation, (2) creating a map of groundwater layer depth distribution (groundwater contour). The stages of this study, namely: (1) equipment preparation, (2) The conjectives of the type of prisoner geoelectric with Schlumberger configuration, (3) The collection of field data, (4) Analysis and interpretation of field Â data. Based on the results of analysis and discussion, can be concluded several things, namely: (i) water carrying layer in location I (TG-01) is suspected to be found in the TUFA layer of Andesit with a depth of 25-61 meters and a layer of andesite Breksi with a depth of more than 61-100.0 meters, (ii) flow of water through intergrain space and cracks/gaps with the potential of small water/until moderate.